1999
DOI: 10.1051/rnd:19990208
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiological consequences of two different weaning methods in sheep

Abstract: -Weaning is associated with a break in the mother-infant contact. In sheep, under natural conditions, the rupture of the social bond is progressive. In contrast, weaning imposed by breeders may result in psychobiological disturbances. The aim of this experiment was to measure the behavioural, hormonal and immune consequences of two types of sudden weaning: total separation (TS) and partial separation (PS) ovins / sevrage / psychobiologie / bien-être

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 18 publications
3
28
2
7
Order By: Relevance
“…There is considerable interest in the welfare of livestock animals during mother-young separation (Orgeur et al 1999), and measures of laterality may provide a useful biomarker of underlying emotional processes during weaning and similar events. In sheep, the ewe-lamb bond is very strong, especially up to 90-100 days after parturition (Galeana et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable interest in the welfare of livestock animals during mother-young separation (Orgeur et al 1999), and measures of laterality may provide a useful biomarker of underlying emotional processes during weaning and similar events. In sheep, the ewe-lamb bond is very strong, especially up to 90-100 days after parturition (Galeana et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In neonatal piglets, the repeated separation from mothers increases basal adrenocorticotrophin (ACTH) and cortisol concentration [6] In sheep under natural conditions, the rupture of the social connection may have long-term consequences, therefore, the weaning imposed by breeders may result in psychobiological disturbances. Separation of lambs from mothers causes behavioral alterations, some hormonal and immune changes and reduced growth [7,8]. Our recent data have shown that a disruption of preweanling lambs-mother social contact enhanced the release of corticotrophin releasing hormone (CRH) from the median eminence (ME) and attenuates processing and release of ACTH [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lower serum globulin concentration in untreated ewes may reflect a state of immunodeficiency (Allison, 2012), considering that their values reflect hypoglobulinaemia (Hearly and Falk, 1974). Although in recently weaned lambs the susceptibility to gastrointestinal parasites increases (Orgeur et al, 1999), it is possible that P4 treatment may reduce the susceptibility to disease in ewes after weaning. To the best of our knowledge, this is the first complete characterization of the behavioural response of ewes to abrupt weaning of lambs.…”
Section: Discussionmentioning
confidence: 99%